“CAMINHOS PARA DEUS” PROPOSTAS RELIGIOSAS DIVERGENTES E IDENTIDADE DO GRUPO JOANINO: UMA LEITURA EM JOÃO 13.33-14.31 - Roque , Célia Juliano (2015)
The Fourth Gospel presents Jesus through metaphors, being the object of our research the phrase: “I am the way, and the truth, and the life” that is the guiding starting point in search of the identity of the Johannine group. At the end of the first century, the Johannine group sees itself as the faithful heirs of Jesus, now followers of the disciple John (son of Zebedee), who walked with Jesus. The group is not alien to the reality of religious multiplicity of the period, being aware of the conflicts and the divergent ways to God. This shows us how identitary this theme is. From a reading in John 13.33-14.31, our dissertation has as object how the Johannine group receives this message in the imaginary, externalizes it and reacts in everyday life, as well as later groups of Gnosticism — as the Gospel of Truth from the Nag Hammadi Coptic Library, drawn from subsequent reading currents shaping the symbolic-imaginary world, cultivating different belonging characteristics and creating the identity of the Johannine group.